Need for Speed? Exchange Latency and Liquidity - Albert J. Menkveld; Marius A. Zoican (Tinbergen Institute, 2014)
Speeding up the exchange does not necessarily improve liquidity. The price quotes of high-frequency market makers are more likely to meet speculative high-frequency "bandits", thus less likely to meet liquidity traders. The bid-ask spread is raised in response. The recursive dynamic model reveals that there is an additional spread-widening effect as market makers earn higher rents due to economies of scope from quote monitoring. Analysis of a NASDAQ-OMX speed upgrade provides supportive evidence.
Keywords: G11; G12; G14; 330; market microstructure; trading speed; information asymmetry; high-frequency trading